Efforts to Improve Children's Understanding of Medicines through the Little Pharmacist Program: Community Service by Andalas University Students at SDN 05 Padang Sago Elementary School - Syukri, Daimon; Ridwan, Andhini Aurellyta; Giovani, Shofya (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2025)
Drugs are dangerous chemicals that are used to diagnose physiological and pathophysiological systems, restore and improve health. The large number of cases found related to drug abuse is caused by a lack of knowledge about rational drug use, drug storage, and others. Based on this problem, one of the health workers who plays an important role is the pharmacist. “Apoteker Cilik” is a program that promoted by Regular KKN Phase I students at Universitas Andalas in 2025 as an effort to prevent drug abuse and branding the pharmacist profession from an early age. This activity includes the delivery of educational and interactive material regarding the introduction of the pharmacist profession, introduction to drugs, types of drugs, and DAGUSIBU by 2 presenters. At the end of the session, students filled out a questionnaire with the scoring results showing that of the 40 participants who attended, 97% had good knowledge regarding the material that had been presented.